KEBUTUHAN MODUL BERBASIS KETERAMPILAN KOMUNIKASI BAGI MAHASISWA PGSD - Juita Harun, Gustiayu; Fitria, Yanti; Yufriana Devi, Meila; Ridha, Mhd.; Yuza, Arlina (Study program PGSD FKIP Universitas Bung Hatta, 2025)
The development of science and technology has led to numerous changes in the world of education. Higher education, as one of the professional institutions, is obliged to determine the methods, teaching systems, and evaluation of policies that have been enacted. The study aims to describe the urgency and responses of PGSD students to the development of communication skills-based modules for PGSD students. The type of data obtained from qualitative and quantitative data, as reflected in the results of questionnaires distributed at two universities in Padang city. Based on the results of the questionnaire, it was found that on average, PGSD students agreed on the use of modules based on communication skills. The dominant module procurement is more likely to use printed modules. The availability of modules is expected to enable students to learn independently, explore and evaluate their abilities, increase their interests and creativity, develop critical thinking skills, and communicate orally and in writing.